Salivary Cortisol Day Curves in Addison’s Disease in Patients on Hydrocortisone Replacement - Ross, I. L.; Levitt, N. S.; Van der Walt, J. S.; Schatz, D. A.; Johannsson, G.; Haarburger, D. H.; Pillay, T. S. (Hormone and Metabolic Research, 2013)
Using salivary cortisol (SC) measurements, cortisol exposure in Addison’s disease patients on hydrocortisone replacement was determined and compared with healthy controls. Cortisol pharmacokinetics was assessed in 31 patients with Addison’s disease on replacement hydrocortisone doses (median daily dose 20 mg; range 5–50 mg) and 30 healthy control subjects. Saliva samples (n=16) were collected between 08:00 and 00:00 h in 1 day, using a passive drool technique. Cortisol exposure was evaluated by noncompartmental approach. In the patients, cortisol exposure was significantly higher than in controls: median inter-quartile range (IQR) peak cortisol (Cmax) 174.5 (59.3–837.0) vs. 6.50 (4.7–19.3) nmol/l, p=0.0001; area under the curve (AUC) 390.1 (177.1–928.9) vs. 21.4 (14.6–28.4) minutes*nmol/l, p=0.0001, trough cortisol level (Cmin) 0.49 (0.49–0.96) vs. 0.49 (0.49–0.49) nmol/l, p=0.02, occurring at 480.0 (0.1–660.0) vs. 405.0 (180.0–570.0) min, p=0.56. First peak cortisol was 174.5 (53.0–754.7) vs. 6.27 (3.90–8.47) nmol/l, p=0.0001 and second peak cortisol 18.90 (5.22–76.9) vs. 3.12 (1.76–4.79) nmol/l, p=0.0001. The time to first peak cortisol differed between the 2 groups, 30 (30–75) vs. 0.1 (0.1–30) minutes; p=0.0001. At doses studied, hydrocortisone replacement therapy results in cortisol pharmacokinetics being markedly different from endogenous cortisol profiles in healthy control subjects. Addison’s disease patients had significantly higher SC levels compared to healthy control subjects.
Keywords: salivary cortisol; addison’s disease; adrenocortical insufficiency; adrenocortical failure